2016
DOI: 10.1007/s11004-016-9642-1
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Earth Surface System Evolutionary Pathways

Abstract: Evolution of Earth surface systems (ESS) comprises sequential transitions between system states. Treating these as directed graphs, algebraic graph theory was used to quantify complexity of archetypal structures, and empirical examples of forest succession and alluvial river channel change. Spectral radius measures structural complexity and is highest for fully connected, lowest for linear sequential and cyclic graphs, and intermediate for divergent and convergent patterns. The irregularity index β represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…While most of the focus in the landscape evolution models remains on tectonic uplift and precipitation patterns, lithology conspicuously emerged as the primary control through our fractal analysis. Further, the topographic characterization through the fractal patterns also presents an opportunity to analyse the inherent nonlinearity in the geomorphic system, as the fractal patterns can be mathematically linked to several forms of nonlinear complexity (Phillips, 2003(Phillips, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the focus in the landscape evolution models remains on tectonic uplift and precipitation patterns, lithology conspicuously emerged as the primary control through our fractal analysis. Further, the topographic characterization through the fractal patterns also presents an opportunity to analyse the inherent nonlinearity in the geomorphic system, as the fractal patterns can be mathematically linked to several forms of nonlinear complexity (Phillips, 2003(Phillips, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…With that, the method is applicable to the results from other (soil-)landscape evolution models or erosion models as well (Temme et al, 2017). Calculating evolutionary pathways is not even limited to soil or geomorphological systems (Phillips, 2016). As long as quantitative spatial and temporal data of model output is present, evolutionary pathways can be determined.…”
Section: Applicability For (Soil-)landscape Evolution Modellingmentioning
confidence: 99%
“…Likewise, debate remains over how to unequivocally discern which data distributions best fit power laws as compared to other, related regression models such as lognormal distributions (e.g., Newman, 2005; Pumain, 2006; McKelvey, 2011, among many others). Different experts have shown evidence that both soil bodies and soilscapes are complex systems (e.g., Phillips, 2013, 2016, 2017) and that they show fractal properties (e.g., Caniego, Ibáñez, & San José, 2006; Ibáñez, Pérez‐Gómez, & San José Martínez, 2009a; San‐José Martínez & Caniego, 2013) (Figure 3a and b). In fact, Phillips (1998) demonstrated that Hans Jenny's factors of soil formation cannot be solved using classical linear mathematical tools, whereas Jenny's state factor equation can be understood in the frame of non‐linear dynamical systems theory.…”
Section: The Nature and Uncertainty Of Power Laws (Natural Artificiamentioning
confidence: 99%
“…In fact, Phillips (1998) demonstrated that Hans Jenny's factors of soil formation cannot be solved using classical linear mathematical tools, whereas Jenny's state factor equation can be understood in the frame of non‐linear dynamical systems theory. We assume that such a link occurs between power laws and complex systems, including the whole earth surface system, such as the structure of drainage basis, landforms and regolith, among many others (e.g., Phillips, 1998, 2016), in view of the fact that most of these resources are also non‐linear and there are numerous interactions between them. Non‐linear and/or complex systems are the product of the interactions between the diverse elements that make up a system.…”
Section: The Nature and Uncertainty Of Power Laws (Natural Artificiamentioning
confidence: 99%